A quantitative study on the water-related energy use in the urban water system of Shenzhen. (May 2022) - Qiu, Guo Yu; Zou, Zhendong; Li, Wenjiang; Li, Linjun; Yan, Chunhua
Highlights: Residential water use is the largest energy consumption of Shenzhen water system. There is a strong nexus between water and energy use in Shenzhen water system. Reducing terminal water use is an effective way to reduce energy consumption. Household water use was mainly affected by family income and water-saving habits. Household electricity use was mainly controlled by family education level. Abstract: A comprehensive understanding of the nexus between urban water and energy is vital for economic development and human survival. Although extensive studies have been conducted on urban water–energy nexus, the nexus is site-specific and governed by many factors. Here, we analyzed water-related energy intensity for residential purpose based on statistical data and family surveys in Shenzhen, which is one of the world's fastest urbanizing megacities facing water and energy scarcity. Then household water and energy use and their main influencing factors were explored. Water-related energy intensity was calculated in kWh/m 3 as follows: source water transfer (0.344), tap water production (0.217), tap water delivery (0.464), residential water use (7.43), wastewater treatment (0.20), and wastewater reuse (0.083). Results show that there's a strong nexus between water and energy in the urban water system. Household water use is mainly affected by family income ( r  = 0.202, p  = 0.002), whereas household electricity use is mainly affected by education level ( r  = 0.191, p  = 0.004). With the projected increases in family size, family income and education level, water and energy supply in Shenzhen are going to face severe challenges.